Muestra iconográfica y documental - Tello Malpartida, Aurelio (2026)
This manuscript brings together a selection of images and documents related to the life and career of the Peruvian composer Celso Garrido-Lecca. It includes photographs of the maestro and his colleagues, records of his Tomás Luis de Victoria Prize, programs, press notes, awards, his discography, and material related to his compositions. Together, these documentary galleries offer a visual journey through the main milestones of his career and constitute a valuable testament to his contribution to contemporary Latin American music.